Emergence and Structural Characteristic of the Solanum pimpinellifolium in Trays under Different Levels and Types of Substrates - Erivaldo Erbo Alves dos Santos; Nathália Maria Laranjeira Barbosa; Francisco Gauberto Barros dos Santos; Antonia Eliene Duarte; Lucas Souza Mateus; Gertrudes Macário de Oliveira; Cristiane Domingos da Paz (Horticulturae, 2023)
The cultivated tomato is one of the most consumed vegetables in the world, and the preparation of seedlings plays a fundamental role in the success of the crop, which is often plagued by fungi and bacteria from its earliest stages. This study aimed to analyze the emergence speed index and morphological parameters of Wanda hybrid cherry tomato seedlings (Solanum lycopersicum var. pimpinellifolium) in trays with two different types and levels of substrates in a protected environment using certified seeds. The experiment was conducted in the greenhouse of the IFCE—Campus Crato during the months of August and September 2022. Two basic substrates were used to promote germination and emergence: one was the commercial Vivato Slim Plus®, and the other was based on worm humus produced in Minhobuckets kits. The experimental design was completely randomized, consisting of five doses of commercial substrate (SBC) and earthworm humus (HDM) in the following proportions: S1—HDM; S2—SBC; S3—HDM + SBC (1:1), S4—HDM + SBC (1:3), and S5—HDM + SBC (3:1). The ESI, morphological parameters (SD, PH, ROOTL, and NL), and the dry biomass of the seedlings (LDB, SDB, RDB, and TDB) were determined. Data were subjected to an analysis of variance, and Tukey’s test (0.05) was used; dry biomass data were submitted to square root transformation. For the emergence speed index, SBC (S2) outperformed the others. Regarding the morphological parameters and dry biomass, all substrates yielded satisfactory results, despite not showing a statistical difference between the averages. The substrate S4 produced the best results in all evaluated parameters.